Polymethoxy Flavonoids, Nobiletin and Tangeretin, Prevent Lipopolysaccharide-Induced Inflammatory Bone Loss in an Experimental Model for Periodontitis - Tsukasa Tominari; Michiko Hirata; Chiho Matsumoto; Masaki Inada; Chisato Miyaura (Elsevier, 2012)
Nobiletin, a polymethoxy flavonoid (PMF), inhibits systemic bone resorption and maintains bone mass in estrogen-deficient ovariectomized mice. This study examined the antiinflammatory effects of PMFs, nobiletin, and tangeretin on lipopolysaccharide (LPS)-induced bone resorption. Nobiletin and tangeretin suppressed LPS-induced osteoclast formation and bone resorption and suppressed the receptor activator of NFκB ligand-induced osteoclastogenesis in RAW264.7 macrophages. Nobiletin clearly restored the alveolar bone mass in a mouse experimental model for periodontitis by inhibiting LPS-induced bone resorption. PMFs may therefore provide a new therapeutic approach for periodontal bone loss. Keywords:: polymethoxy flavonoid, inflammatory bone resorption, periodontal disease